1899 Wyo. Rev. Stat. 1253, div. 5, tit. 1, ch. 3, § 5052 - (:unkn) unknown (General Publisher, 1899)
It shall be unlawful for any person to sell, barter or give to any other person under the age of twenty-one years any pistol, dirk or bowie knife, slung-shot, knucks or other deadly weapon that can be worn or carried concealed upon or about the person, or to sell, barter or give to any person under the age of sixteen years any cartridges manufactured and designed for use in a pistol; and any person who shall violate any of the provisions of this section shall be fined in any sum not more than fifty dollars.
--
Keywords: TRANSFER - MINORS